Succinum extracts inhibit microglial-derived neuroinflammation and depressive-like behaviors - Kang, Ji-Yun; Baek, Dong-Cheol; Son, Chang-Gue; Lee, Jin-Seok (Frontiers in Pharmacology, 2022)
Microglia are emerging as important targets for the treatment of neuropsychiatric disorders. The phagocytic microglial phenotype and the resulting neuroinflammation lead to synaptic loss and neuronal cell death. To explore potential candidates that inhibit microglial hyperactivation, we first investigated ten candidate extracts of traditional Chinese medicine (TCM) using lipopolysaccharide (LPS)-stimulated BV2 microglial cells. Among the candidates, Pinus spp. succinum extract (PSE) was superior; thus, we further investigated its pharmacological activity and underlying mechanisms both in vitro and in vivo. Pretreatment with PSE (10, 20, and 40 μg/mL) attenuated the increases in inflammatory factors (nitric oxide and tumor necrosis factor-α), translocation of nuclear factor-kappa B (NF-κB), and phenotypic transformations (phagocytic and migratory) in a dose-dependent manner. These inhibitory effects of PSE on microglia were supported by its regulatory effects on the CX3C chemokine receptor 1 (CX3CR1)/nuclear factor erythroid-2-related factor 2 (Nrf2) pathway. In particular, intragastric administration of PSE (100 mg/kg) considerably improved sickness, anxiety, and depressive-like behaviors in mice subjected to chronic restraint stress (CRS). Our results suggest that PSE has strong antineuroinflammatory and antidepressant properties, and the underlying mechanisms may involve not only the regulation of NF-κB translocation but also the normalization of the CX3CR1/Nrf2 pathway.